Analisis Kestabilan Model Host-Vector Transmisi HIV/AIDS Pada Pengguna Jarum Suntik - Jafaruddin (Alm); Rapmaida M. Pangaribuan; , Aryanto; Irena A. Henukh (Jurnal Matematika, 2017)
HIV/AIDS is a very dangerous disease. The transmission of HIV/AIDS can be in three ways and one of them through a syringe. In this paper we describe SIR and SEIR Host-Vector model transmission of HIV/AIDS amongst populations of injecting drug users. From the existing model we obtained disease-free equilibrium point and endemic equilibrium point. Then we study the stability conditions and sensitivity analysis of the . The analysis shows if then the disease-free equilibrium point is stable and if then the endemic equilibrium point will be stable. We also obtained that parameter of probality host-vector infected with HIV/AIDS affects the increase of number infected HIV/AIDS. Keywords: HIV/AIDS, Host-Vector Transmission, The Stability of Equilibrium Point.